2010
DOI: 10.4315/0362-028x-73.11.2089
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Escherichia coli O157:H7 in Horses in Ohio, USA

Abstract: Manure from draft animals deposited in fields during vegetable and fruit production may serve as a potential source of preharvest pathogen contamination of foods. To better quantify this risk, we determined the prevalence of Escherichia coli O157:H7 in horses. Between June and September 2009, freshly voided fecal samples were collected from horses stabled on 242 separate premises in Ohio, USA. Overall, the prevalence of E. coli O157:H7 was 1 of 242 (0.4% prevalence, 95% confidence interval [CI] = 0.01 to 2.28)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
1
15
0
4
Order By: Relevance
“…Interestingly, this case shared housing accommodations with a goat that also shed STEC O157. The isolates from both animals had indistinguishable multiple-locus variable number tandem repeat analysis patterns (87). A similarly low prevalence has been reported by Hancock et al, who reported that 1% of horses sampled (n = 90) tested positive for O157:H7 (85).…”
Section: Equinesupporting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, this case shared housing accommodations with a goat that also shed STEC O157. The isolates from both animals had indistinguishable multiple-locus variable number tandem repeat analysis patterns (87). A similarly low prevalence has been reported by Hancock et al, who reported that 1% of horses sampled (n = 90) tested positive for O157:H7 (85).…”
Section: Equinesupporting
confidence: 73%
“…There are also no published case reports describing the clinical features of STEC infection in horses. The available published data on the prevalence of STEC in horses (85)(86)(87)(88) and donkeys (84,89,90) indicate that they are not major reservoirs of STEC and may instead be spillover hosts. Only one of 400 horse fecal samples screened in Germany was positive for STEC.…”
Section: Equinementioning
confidence: 99%
“…Horses, particularly foals, may therefore not be important reservoirs or carriers of this serotype of E. coli in Trinidad. E. coli O157, which is a cause of haemorrhagic diarrhoea in humans [37], has been reported by others to be isolated from the faeces of horses at a low frequency of 0.4% [38] but at a higher rate (12.3%) from horse farm environments [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Cattle seem to lack vascular receptors for shiga-like toxins (Pruimboom-Brees et al, 2000). E. coli O157:H7 has also been isolated from other animals including deer (Diaz et al, 2011), sheep (Urdahl et al, 2003), horses (Lengacher et al, 2010), goats (Mersha et al, 2010), and dogs (Kataoka et al, 2010). …”
Section: General Characteristics Of E Coli O157:h7mentioning
confidence: 99%